Personality, social hierarchy and hormones in primates - Konečná, Martina (Jihočeská univerzita, 2010)
This thesis deals with two main issues: personality (stable individual differences in behavior) and behavioral endocrinology (or socioendocrinology) in nonhuman primates. The first part of the thesis comprises of two primate personality studies of two species: Hanuman langurs and Barbary macaques. Two basic methods of animal personality research (behavioral coding and trait rating) were compared. Stability of personality assessments has been demonstrated. Social rank of individuals was used to validate the questionnaire ratings as well as to illustrate the independence and stability of personality assessment. The second part of the thesis is based on two studies investigating hormone levels in female Barbary macaques. The relationship between cortisol, testosterone, dominance hierarchy and behavior was investigated. And the possible effect of maternal hormone levels around the time of conception on the sex of an infant was evaluated.
Personality, social hierarchy and hormones in primates
Keywords: animal personality; social dominance; testosterone; cortisol; Barbary macaques; Hanuman langurs; animal personality; social dominance; testosterone; cortisol; Barbary macaques; Hanuman langurs